Immune mechanisms and possible immune therapy in testicular germ cell tumours. (6th June 2019) - Chovanec, M.; Mardiak, J.; Mego, M.
Abstract: Background: Testicular germ cell tumours (GCTs) are the only universally curable solid malignancy. The long‐term cure rate of >95% is attributed to the extraordinary sensitivity to cisplatin‐based treatment but a proportion of patients die due to a progression of the chemotherapy‐refractory disease. While treatment of a variety of solid cancers was significantly improved with recent immune therapies, the immunology and immunotherapy remained underinvestigated in GCTs. Objectives: In this narrative review, we summarize evidence about immune‐related mechanisms and possible immune therapies in GCTs and provide insights and implications for future research and clinical practice. Materials and methods: We performed a comprehensive search of PubMed/MEDLINE to identify original and review articles reporting on immune mechanisms and immunotherapy in GCTs. Review articles were further searched for additional original articles. Results: Clear link of immune surveillance and the presence of GCT have been identified with several novel immune‐related prognostic biomarkers published recently. Several case reports, case series, and preliminary results from phase I‐II studies are emerging to report on the efficacy of immune checkpoint inhibitors. Discussion: Newly discovered immune biomarkers provide an evidence supporting the role of immune environment in the GCT biology. While these discoveries provide only an initial insight into the immunobiology, strong correlation with prognosis is evident. This provided a premise to investigate the treatment efficacy of novel immunotherapy. Some efficacy of these treatments has been reported in clinical setting; however, the results of published studies with immune checkpoint inhibitor monotherapy seem to be disappointing. Conclusion: Immune‐related mechanisms and efficacy of immune checkpoint blockade in GCTs should be further investigated in preclinical and clinical studies.